2007
DOI: 10.1007/s11595-006-3522-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure and dielectric properties of doped BaTiO3 ceramics

Abstract: The effects of two rare earth oxides such as CeO 2 and Sm 2 O 3 on the phase structure and dielectric properties of BaTiO 3 ceramic were investigated. Results indicate that the dielectric constant of this system will increase greatly with the increasing content of these two oxides, and Ce 4+ substitutes for Ba 2+ located at A-site in ABO 3 structure. Quantitative XRD analysis shows that c/a ratio in the sample with addition of CeO 2 will increase, which implies the increase of tetragonality in system, causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Various oxide materials have been reported as gate dielectric for GaN MOS‐HEMTs. For example, Si 3 N 4 deposited by in situ metalorganic chemical vapor deposition (MOCVD) , Al 2 O 3 deposited by MOCVD or atomic layer deposition (ALD), HfO 2 deposited by ALD and SiO 2 deposited by ALD or plasma enhanced chemical vapor deposition . Among these, Al 2 O 3 and SiO 2 have been two of the most suitable oxides owing to their relatively large conduction band offset (CBO) with GaN and large breakdown electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Various oxide materials have been reported as gate dielectric for GaN MOS‐HEMTs. For example, Si 3 N 4 deposited by in situ metalorganic chemical vapor deposition (MOCVD) , Al 2 O 3 deposited by MOCVD or atomic layer deposition (ALD), HfO 2 deposited by ALD and SiO 2 deposited by ALD or plasma enhanced chemical vapor deposition . Among these, Al 2 O 3 and SiO 2 have been two of the most suitable oxides owing to their relatively large conduction band offset (CBO) with GaN and large breakdown electric field.…”
Section: Introductionmentioning
confidence: 99%
“…If interface charges at the oxideAlInN interface are neglected, the threshold voltages of the untreated ('V th,HFET ') and the oxidized samples ('V th,MIS ') can be related by [6,9] , (1) where d oxide and d barrier are the thicknesses of the oxide and barrier layer, respectively, with the according dielectric constants ε oxide and ε barrier . The term n S,MIS /n S,HFET accounts for the different sheet carrier concentrations observed in the untreated ('HFET') and oxidized ('MIS') samples.…”
Section: Contributedmentioning
confidence: 99%
“…Effective gate leakage suppression has been realized by applying a thin dielectric layer underneath the gate metallization, thus replacing the Schottky gate by a metalinsulator-semiconductor (MIS) structure. Various insulators like SiO 2 [2,4,5], SiN [2,6], Al 2 O 3 [7] and, most recently, high-k oxides [8,9] are currently under detailed investigation. The so-called MIS-HFETs have shown improved device properties in terms of 2DEG density, 2DEG mobility, gate leakage current suppression, device stability as well as high-power / high-frequency capability [2,10].…”
mentioning
confidence: 99%
“…Zhang Aiqin 4 and others studied the polyaniline under hydrochloric acid doping with high-specific capacitance and good cycling performance. Li Junjie 5,6 and others studied the conductivity of polyaniline under the doping of perchloric acid, sulfuric acid, p-toluene sulfonic acid and camphor sulfonic acid solutions and found that the conductivity of p-toluene sulfonic acid was the best. Wang Ye 7 and others studied polyaniline under different concentrations of nitric acid and hydrochloric acid doping and found that the hydrochloric acid doped polyaniline was better than nitric acid in terms of crystallinity and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%